The Political Communication of H. Syamsul Arifin, SE in Constructing a Positive Image Across Ethnic Communities in North Sumatra Province - Siagian, Muhammad Daud; Katimin, Katimin; Kustiawan, Winda (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to analyze the political communication of H. Syamsul Arifin, SE in building a positive image among cross-ethnic communities in North Sumatra. As a region with a high degree of ethnic diversity, politics in North Sumatra requires an inclusive communication approach capable of embracing various community groups. Within this context, H. Syamsul Arifin is recognized as a political figure who successfully developed a leadership image accepted by multiple ethnic groups, earning him the title Friend of All Ethnicities. This makes it compelling to further examine the political communication strategies he employed. The study adopts a qualitative approach using case study and discourse analysis methods, focusing on Syamsul Arifin’s political communication in diverse settings, including mass media, direct interaction with the public, and political campaigns. Data were collected through in-depth interviews, document analysis, and observation. The findings indicate that the success of Syamsul Arifin’s political communication was rooted in his ability to build interpersonal communication, sensitivity to local culture, and dialogical approaches that prioritized feedback from the community. His strategies reflect the two-way symmetrical communication model (James Grunig) and high-context communication (Edward T. Hall), which highlight the importance of cultural context in delivering political messages. Communication barriers such as ethnic differences, social stereotypes, and perception gaps were effectively addressed through participatory approaches, the use of local cultural symbols, and the involvement of community leaders. Indicators of success include cross-ethnic acceptance, increased political participation, and the establishment of public trust in his leadership. These findings reinforce the importance of culture-based political communication in plural societies.